Sex-related variation of neurocognitive functioning in bipolar disorder: Focus on visual memory and associative learning. (September 2018) - Tournikioti, Kalliopi; Ferentinos, Panagiotis; Michopoulos, Ioannis; Dikeos, Dimitris; Soldatos, Constantin R.; Douzenis, Athanasios
Highlights: Visual memory and associative learning have been less researched in bipolar disorder (BD). Few studies have examined sex effects on cognition despite its clinical relevance. A diagnosis-specific sex effect was found for two separate tasks of visual memory/learning pointing to an attenuation of the normal sex-related variations in bipolar men. Sex-related variation of cognition in healthy subjects is disrupted in BD. ABSTRACT: Bipolar disorder (BD) is associated with cognitive deficits in attention, verbal memory and executive functions. However, only few studies have examined sex effects on cognition despite their clinical relevance. Given that visual memory/ learning has been understudied the aim of our study was to investigate sex-related variation in cognition( executive functions and visual memory/ learning) in BD. Cognitive performance of 60 bipolar-I patients and 30 healthy controls was evaluated by using CANTAB battery tasks targeting spatial memory (SRM), paired associative learning (PAL) and executive functions. We fitted a multivariate analysis of covariance (MANCOVA), followed by task-specific ANCOVAs. A significant diagnosis by sex interaction effect was detected (MANCOVA); specifically, diagnosis-specific sex effects were found for SRM and PAL, as healthy males outperformed healthy females but this pattern was attenuated in BD patients. Patients' clinicodemographic characteristics, current psychopathology or medication status did not differ across sexes and were, therefore, unlikely to explain detected sex effects. Our study is one of few studies to assess sex-related variation in cognition in BD and the first to record a diagnosis-specific sex effect for two tasks of visuo-spatial memory/ learning, indicating that sex-related variation in healthy subjects is disrupted in BD.